Emerging Trends in East Asia : New Directions in the World Bank's Partnership - Wolfensohn, James D. (2016)
James D. Wolfensohn, President of the World Bank Group, remarked that despite remarkable successes, East Asian countries face formidable challenges in sustaining their development in the face of large-scale changes taking place throughout the region. Increasingly, countries of the region confront common development policy challenges. Their common agenda must be the agenda of the World Bank Group if the Bank is to remain relevant to them. Responding effectively to these needs will require that the Bank Group forge new partnerships and revitalize traditional ones.